Coastal Dynamics and Territorial Zoning - Brenes, Luis Guillermo (2005)
Coastal spaces are very dynamic forms, they include the area of direct marine action or intertidal zone, including the fossilized features that are conserved as testimony of the changes in the relative sea level, this by tectonic or  climatic  factors  that  have  taken  place  during  the Quaternary. In addition, this concept includes the set of activities that on some way depend on the sea or are related to it, like fisheries, salt mines, shipyards, fishermen’s residential areas, hotels and recreational sites associated to the use of the marine resources, extending that boundary to limits very difficult to show in the continental areas. It  is  important  to  know  the  dynamics  of  these  spaces and the changes induced by the man in order to handle them suitably. Costa Rica has in the regulating plans an instrument for the management of those spaces, but it is necessary to incorporate the coastal variable to improve the use of those landscapes. The geographers have made progress in the knowledge and study of that significant strip and have contributed with their knowledge to the process of land management by means of techniques and procedures that reveal the most important characteristics of the coastal environment.